Effect of Mothers' Participation in Preterm Infants' Care in NICU on Readmission Rates - T Aliabadi; F Bastani; H Haghani (Tehran University of Medical Sciences, 2011)
Background & Aim: Despite technology development, rate of infants' hospitalizations is still high, which endures emotional and economic burden to families. The aim of this study was to investigate the effect of mothers' participation in care of preterm infant on readmission rate.Methods & Materials: In this randomized controlled trial, 100 mothers who had preterm infants (gestational ages: 30-37 weeks) with respiratory distress syndrome were recruited. Samples were selected using continuous random assignment. Collaborative programs for the intervention group were implemented in the form of an information session and presence and participation of mothers in their infants care. One month after discharge, readmission check list was completed. Data were analyzed using Chi-square and paired t tests.Results: Results showed that readmission rate was lower in the intervention group compared with the control group. The average length of stay in hospital was 6.96 in the intervention group and 12.96 in the control group (P<0.00).Conclusion: Participation of mothers in care of their infants reduced readmission rate.